Developments In Orthodontıc Cements - İlken Kocadereli (Galenos Yayinevi, 1994)
In this literature review dental cements which were used for banding orthodontic attachments to teeth were evaluated. The general properties of zincphosphate cement, polycarboxylate cement and recently developed glass ionomer cements were discussed.